The compatibility analysis of subject matter description with basic competence at science textbook for 7th grade of junior high school - F Hidayat; P Sinaga; Hernani Hernani (International Journal of Science and Applied Science: Conference Series, 2017)
The aim of this research is to analyze the quality of science textbooks for 7th grade of Junior High School in Bandung City. This research use content analysis method and data analysis with quantitative descriptive analysis technique. The compatibility analysis of subject matter description with basic competence use instrument which adopted from the instrument of BSNP and based on three indicators, (1) completeness, (2) broadness, and (3) deepness. Completeness based on the presentation of subject matter, broadness based on the presentation of concept, definition, procedure, or example which support to the subject matter, and deepness based on subject matter explanation. The samples are one electronic textbook (BSE), be code in A and two non-electronic textbooks (non-BSE), be code in B and C. The samples selected by purposive sampling technique. Analysis result shows that the completeness of book A, B, and C are 100%, 96,15%, and 96,15% consecutively. The broadness of book A, B, and C are 100%, 88,46%, and 84,62% consecutively. The deepness of book A, B, and C are 92,31%, 88,46%, and 73,08% consecutively. So, book A (BSE) have better quality than book B and C (non-BSE).